Persepsi masyarakat terhadap agroforest karet sebagai alternatif pengelolaan sumberdaya hutan yang lestari: (studi kasus di desa Lubuk Beringin, kec. Rantau Pandan, kab. Bungo, Jambi) - Muntasyarah, A.S. (Gadjah Mada University, Faculty of Forestry, 2005)
Rubber plantations management on rubber agroforest form is a form of utilization and management of forest resource which is practised specifically by the Bungo community. On the rubber agroforest, the communities mix agriculture and forestry plants on the field they have, trying to mix short and long term concerns. The objective of this research is to find out community perception on rubber agroforest and their interaction with the rubber agroforest. The method used in this research is descriptive method with qualitative and quantitative approach. Data collection was done by observation, deep and half structured interview, "kampung" discussion and transect to collect data on biodiversity. The result of the research shows that rubber agroforest is a form of symbolic interaction of the community with the forest resource and social object around them. Rubber agroforest means as the source of main income for the community and also as a part of their lives. On the rubber agroforest, they can fulfil about 70% of their needs, so the perception built in the mind of Lubuk Beringin community is that rubber plantation has economic value. But their economic view is also able to mix the need on sustainable result and sustainable environment. Communities do not only take care of the rubber plants on their rubber agroforest field, but also other plants, especially fruit plants. The result of this economi view forms a rubber agroforest which is very similar to forest, with vegetation structure like secondorary forest and high enough biodiversity leverl, it is not only flora biodiversity exists. Rubber agroforest can be one of the alternatives of sustainable fores resource management which is specific to a region.